Frequency distribution of geomagnetic disturbance commencements at Alibag for the period 1921-1960 (MAUSAM, 1966)
Frequency distribution of times of commencement of geomagnetic disturbances at Alibag is studied. Hourly distribution of SSC (Storm Sudden Commencement) occurrences does not show any significant diurnal variation, however, a broad tendency for the frequency to be slightly higher during the day than the night is noticed. Hourly distribution of GC's (Gradual Commencements) show 8, definite preference for the hours 6 to 12 local time, with 50 per cent occurring during that interval. Monthly distribution of both SSC and GO occurrences show a slightly higher frequency for the equinoxial months.